Okręg Stanisławów Armii Krajowej .......... 143 - Dudek, Tomasz (Kresowi żołnierze Armii Krajowej: Historia – Polityka – Pamięć, 2024)
THE HOME ARMY STANISŁAWÓW DISTRICTThis section discusses the history of the ZWZ-AK (The Home Army Union of Armed Struggle) in its Stanisławów district during World War Two. In this paper, the author attempted to showcase the operations of individual units of the Polish underground resistance organisation in the Stanisławów area which targeted the Soviets, the Germans, and the Ukrainians, as well as to reconstruct the staffing of the Stanisławów district structures. The author did not ignore an important, yet little known issue of the Polish civilian self-defence organised against Ukrainian nationalists targeting the Polish population with criminal acts in the Stanisławów area. It was the Polish self-defence operatives who allowed large clusters of Polish population to survive. In the final part of the section, the author discussed the course of Operation Tempest and attempted to reconstruct the underground resistance structures under the new occupational force, the Soviets. The author noted that after the Soviets established control over the area, a very high number of Home Army soldiers entered service in ‘instrebityel (hunter) battalions’ tasked with protection of the local population against the terror of the UPA.